2001
DOI: 10.1038/sj.bjp.0703777
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological block of the slow component of the outward delayed rectifier current (IKs) fails to lengthen rabbit ventricular muscle QTc and action potential duration

Abstract: 1 The eects of I Ks block by chromanol 293B and L-735,821 on rabbit QT-interval, action potential duration (APD), and membrane current were compared to those of E-4031, a recognized I Kr blocker. Measurements were made in rabbit Langendor-perfused whole hearts, isolated papillary muscle, and single isolated ventricular myocytes. 2 Neither chromanol 293B (10 mM) nor L-735,821 (100 nM) had a signi®cant eect on QTc interval in Langendor-perfused hearts. E-4031 (100 nM), on the other hand, signi®cantly increased Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 39 publications
9
83
1
Order By: Relevance
“…18,19 As with chromanol 293B in guinea pig, considerable prolongation of APD remains at short cycle length. 20 The extent of APD prolongation by chromanol 293B (23% to 31%) is comparable to that reported in single ventricular myocytes of guinea pig and humans 6 but much greater than that observed in multicellular ventricular tissue preparations of guinea pig, 21 rabbit, 22 and dog. 23 Different intracellular milieus might be involved in the discrepancy.…”
Section: Comparison Between the Effects Of Chromanol 293b And Other Csupporting
confidence: 59%
“…18,19 As with chromanol 293B in guinea pig, considerable prolongation of APD remains at short cycle length. 20 The extent of APD prolongation by chromanol 293B (23% to 31%) is comparable to that reported in single ventricular myocytes of guinea pig and humans 6 but much greater than that observed in multicellular ventricular tissue preparations of guinea pig, 21 rabbit, 22 and dog. 23 Different intracellular milieus might be involved in the discrepancy.…”
Section: Comparison Between the Effects Of Chromanol 293b And Other Csupporting
confidence: 59%
“…4A and 4B). Previous studies have suggested that chromanol 293B-induced inhibition of IKs has only minimal effects on an in vitro system, when measuring APD in various species, including rabbit, without β-adrenergic stimulation [16][17][18]. Consistent with these findings, our recordings also showed that chromanol 293B alone had no effect on APD (Control: 381.6±15.1 ms, chromanol 293B: 380.5±18.3 ms) (Fig.…”
Section: Aip1 Increased Activity Of Ikr Rather Than Iks In Ventriculsupporting
confidence: 81%
“…However, APD 90 response to increases in these currents was relatively modest, such that substantial increase would be required to impact the adaptation to baseline. The I Kr current was not increased, as the model APD 90 prolongation due to I Kr inhibition was very similar to that recorded experimentally for a pure I Kr blocker [4]. The I tos current was also determined to be unsuitable due to the strongly reverse rate dependent impact on APD 90 .…”
Section: Discussionmentioning
confidence: 56%